Propagation, scattering and dissipation of electromagnetic waves - Ilyinski, A. S.; Slepyan, G. Ya.; Slepyan, A. Ya. (London P. Peregrinus on behalf of the Institution of Electrical Engineers, 1993)
The following topics are dealt with:surface-impedance technique; dissipation processes; finite conductivity; waveguides; resonators; electromagnetic-wave diffraction; eigenmodes; anisotropic media; and finitely conducting walls.
Electronic reproduction.
Keywords: Electromagnetic waves; Electronic books